Smart Drip Irrigation System with Integrated Soil pH and Moisture Sensors Using RS485 Communication - Muhammad Rafindha Aslam; Faisal Candrasyah Hasibuan; Rifqi Muhammad Fikri (LPPM Universitas Islam 45 Bekasi, 2025)
Agricultural development requires reliable methods for measurable soil condition monitoring to support crop growth. Soil moisture and soil pH are critical parameters that significantly affect plant development. Manual observation of these parameters is inefficient and often produces inconsistent data. This study designed a smart drip irrigation system integrating soil moisture and soil pH sensors with RS485 communication using the MAX485 module. Arduino Nano was applied as the sensor node for data acquisition, and ESP32 was used as the master controller for decision-making in irrigation and fertilization. System validation employed Lavios VT-05 as the reference instrument. Experimental results showed that soil moisture sensors provided consistent readings with minimal deviation across different conditions, while soil pH sensors maintained high accuracy compared to standard buffer solutions. RS485 communication was tested up to 7 meters and demonstrated stable performance. These findings confirm that the system is capable of accurate soil monitoring and reliable communication for smart drip irrigation applications.